Technical, Political, and Social Issues in Archaeological Collections Data Management. Issue 3 (August 2019) - Emerson, Patricia; Hoffman, Nancy
Abstract: Managing collections means ensuring that the data about them are useful, available, and accurate. In addition to the technical aspects of data management, there are layers of political and social structure that direct the construction and use of collections data. The Minnesota Historical Society (MNHS) employs a set of data standards that allows us to gather electronic cataloging data from a wide community of archaeology researchers who are depositing collections at our institution. Though met with initial resistance, these standards have facilitated publication in Open Context as linked open data. Furthermore, institutional discussions concerning Creative Commons licensing and the cultural sensitivity of collections data were precipitated by publication, highlighting the role of social agreement in data management. We found that successful employment of data standards must take into account the needs of the various stakeholders and further their interests. Standards will be most useful and successful when they are lightweight, are supported by training and documentation, and exist as part of a system that allows for more than one way to characterize the collections. Abstract : Administrar colecciones significa garantizar que los datos acerca de estas sean útiles y precisos, y estén disponibles. Además de los aspectos técnicos del manejo de datos, hay capas de estructura política y social que dirigen la construcción y el uso de los datos de las colecciones. La Sociedad Histórica de Minnesota emplea un conjunto de estándares de datos que permite recopilar datos de catalogación electrónica de una amplia comunidad de investigadores de arqueología que depositan colecciones en nuestra institución. Aunque se encontraron con una resistencia inicial, estos estándares han facilitado la publicación en Open Context como datos abiertos conectados. Además, las discusiones institucionales sobre la licencia de Creative Commons, y la susceptibilidad cultural de los datos de colecciones, se precipitaron mediante la publicación, destacando el rol del acuerdo social en el manejo de datos. Establecer los requisitos técnicos fue un reto. Encontrar una forma de representar los datos existentes con precisión, de manera útil y fácil de buscar, ha sido igualmente desafiante. Los estándares serán más útiles y exitosos cuando sean ligeros, estén respaldados por la formación y la documentación, y existan como parte de un sistema que permite más de una manera de caracterizar las colecciones.